Analysis of the Influence of Good Corporate Governance on the Performance of Indonesian Islamic Banks in View from Maqashid Syariah 2015-2019: Analisis Pengaruh Good Corporate Governance Terhadap Kinerja Bank Syariah Indonesia Ditinjau Dari Maqashid Syariah Tahun 2015-2019 - Mochamad Munthaha Firrizqi; Imelda Dian Rahmawati (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study was to determine and analyze the effect of of good corporate governance as proxied by the board of commissioners, board of directors, audit committee and institutional ownership on the performance of Islamic banks in terms of Islamic maqashid. Another research objective is to determine the ranking of Islamic commercial banks in 2015-2019. The research was conducted using quantitative methods with multiple linear regression analysis techniques. The study was conducted using 10 samples with the amount of data observed as many as 50 financial reports. The results showed that the audit committee had a significant effect on the performance of Islamic banks, while the board of commissioners, board of directors and institutional ownership had no significant effect on the performance of Islamic banks. Simultaneously, it shows that good corporate governance has a significant effect on the performance of Islamic banks period 2015-2019.